Technostress in Nursing Education: A Scoping Review. - Lobão, Catarina; Coelho, Adriana; Parola, Vitor; Neves, Hugo; Pereira Sousa, Joana; Gonçalves, Rui (Nursing Reports, 2025)
Technological advancement has radically transformed higher education, requiring faculty members to continually adapt to new tools and teaching methods. In this context, the phenomenon of fear of missing out (FoMO) has gained relevance, often manifesting through a range of negative emotional states, including technostress—stress associated with the use of technology. Objectives: This study aimed to map the available scientific evidence on technostress among nursing faculty in higher education, through a scoping review conducted according to the methodology proposed by the Joanna Briggs Institute (JBI). Methods: The literature search was performed across eight databases, including Medline (via PubMed), CINAHL Complete, Scopus, and the Teacher Reference Center. Results: Of the 266 studies identified, only 3 met the inclusion criteria. Conclusions: Findings reveal varying levels of technostress among nursing educators, with higher levels observed among older faculty members, frequently associated with limited technical and administrative support. Although the direct impact on job satisfaction was not significant, the anxiety induced by intensive technology use and the perceived necessity for constant professional updating—often driven by FoMO—was shown to affect daily academic life, highlighting the need for effective coping strategies. Understanding technostress within the context of nursing education is essential for addressing the challenges of pedagogical modernization. This review supports the need for future institutional interventions aimed at preventing technostress and fostering a more balanced, reflective, and sustainable relationship with technology in academic settings.